Viva pedagogy. Testimonials. 1. Palma Red - Flores Barboza, José (2014)
Dr.Jose Clemente Flores Barboza, distinguished professor of our faculty, this issue begins a series of stories of high school. The passages are presented experiences from his own life story and that of their students, and are cause for reflection, debate and research. In this sense, providing important input for the training of future teachers through the case method, who sedissemination strategy has devoted much of his valuable work.